Sex and age differences in ICD-11 PTSD and complex PTSD: An analysis of four general population samples. Issue 1 (4th October 2021) - McGinty, Grainne; Fox, Robert; Ben-Ezra, Menachem; Cloitre, Marylène; Karatzias, Thanos; Shevlin, Mark; Hyland, Philip
Abstract: Background: Posttraumatic stress disorder (PTSD) is traditionally understood as a disorder that occurs more commonly in women than in men, and in younger age groups than in older age groups. The objective of this study was to determine if these patterns are also observed in relation to International Classification of Diseases (ICD-11) PTSD and complex PTSD (CPTSD). Methods: Secondary data analysis was performed using data collected from three nationally representative samples from the Republic of Ireland ( N  = 1, 020), the United States ( N  = 1, 839), and Israel ( N  = 1, 003), and one community sample from the United Kingdom ( N  = 1, 051). Results: Estimated prevalence rates of ICD-11 PTSD were higher in women than in men in each sample, and at a level consistent with existing data derived from Diagnostic and Statistics Manual of Mental Disorders (DSM)-based models of PTSD. Furthermore, rates of ICD-11 PTSD were generally lower in older age groups for men and women. For CPTSD, there was inconsistent evidence of sex and age differences, and some indication of a possible interaction between these two demographic variables. Conclusions: Despite considerable revisions to PTSD in ICD-11, the same sex and age profile was observed to previous DSM-based models of PTSD. CPTSD, however, does not appear to show the same sex and age differences as PTSD. Theoretical models that seek to explain sex and age differences in trauma-related psychopathology may need to be reconsidered given the distinct effects for ICD-11 PTSD and CPTSD.